2007
DOI: 10.2174/157017907782408770
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Complexes of Some Azamacrocycles and Their Use in Molecular Recognition

Abstract: Azamacrocycles show high affinity for the complexation of a wide range of transition metals. By additional reversibly coordinated ligands, these metal complexes have shown to be interesting tools for molecular recognition, especially for biological systems. Herein, the role of metal complexes of 1,4,8,11-tetraaza-cyclotetradecane ([14]aneN4 or cyclam), 1,4,7,10-tetraaza-cyclododecane ([12]aneN4 or cyclen), 1,5,9-triaza-cyclododecane ([12]aneN3), 1,4,7-triaza-cyclononane ([9]aneN3 or TACN) is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…A green complex was isolated after reaction of 4,7-bis(2-hydroxyethyl)-1-thia-4,7diazacyclononane ( Figure 37 Fitting of the variable temperature susceptibility data (4 -300 K) with the Bleaney-Bowers [196] equation indicated that the two copper(II) sites were non-interacting (2J = -0.001 cm -1 ) [75]. EPR spectroscopy was consistent with a single paramagnetic d 9 The IR spectrum shows two bands at 2246 cm -1 and 2150 cm -1 ; the peak at lower frequency shifted to lower energy on 13 Figure 47) [197]. The crystal structure revealed a distorted octahedral geometry around the metal ion with the cyclononane macrocycle occupying one face of the metal.…”
Section: Copper(ii) Silver and Gold(iii)mentioning
confidence: 95%
See 1 more Smart Citation
“…A green complex was isolated after reaction of 4,7-bis(2-hydroxyethyl)-1-thia-4,7diazacyclononane ( Figure 37 Fitting of the variable temperature susceptibility data (4 -300 K) with the Bleaney-Bowers [196] equation indicated that the two copper(II) sites were non-interacting (2J = -0.001 cm -1 ) [75]. EPR spectroscopy was consistent with a single paramagnetic d 9 The IR spectrum shows two bands at 2246 cm -1 and 2150 cm -1 ; the peak at lower frequency shifted to lower energy on 13 Figure 47) [197]. The crystal structure revealed a distorted octahedral geometry around the metal ion with the cyclononane macrocycle occupying one face of the metal.…”
Section: Copper(ii) Silver and Gold(iii)mentioning
confidence: 95%
“…The ligand showed a stronger "OFF-ON" CHEF effect in the Zn(II) complexes than in the Cd(II) complexes [197]. The The complex displays a five-line 13 and a trigonal prism [198]. The N 2 S planes of the respective ligands are rotated by 89° from the eclipsed positions with the coordination polyhedron expanded in the direction orthogonal to the ligand planes [198].…”
Section: Copper(ii) Silver and Gold(iii)mentioning
confidence: 98%
“…[15] Transition metal complexes have much to offer in the realm of the molecular machine, and to supramolecular chemistry more generally. [16][17][18][19][20][21] Metal complexes of azamacrocycle ligands have been used for molecular recognition, [22,23] in av ariety of biomimetic systems, [24][25][26] and as molecular switches. [27][28][29][30][31][32][33][34][35] The terms "scorpiand" and more recently "scorpionand" have been appliedt od escribe macrocycles bearing am ovable pendant arm whose coordination properties may be alteredb ye xternal input (based on the likeness to an 'aggressive molecular "tail" that "stings"t he chelated metal centre from the top').…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zn(II) complexes with macrocyclic polyamines as 1,4,7-triazacyclononane (tacn), 1,4,7,10-tetraazacyclododecane (cyclen) and 1,4,8,11-tetraazacyclotetradecane (cyclam) were tested for molecular recognition of nucleotides, amino acids and their peptides. Utilization of metal complexes with the azacycles was reviewed by Kőnig (Geduhn et al, 2007). On the basis of a number of examples from the literature, authors documented that complexes of transition metal ions with the azacycles are very stable, both thermodynamically and kinetically, in contrast to the reversible coordination of an incoming bioligand, and thus, the azacycle complexes could be a tool for the molecular recognition.…”
Section: Introductionmentioning
confidence: 99%